Implementasi Kerja Sama Keantariksaan (Indonesia-Tiongkok) Menggunakan Skema 4 Paralel Mission - Tria Wahyu Artita; Tiofani Naura Br. Tobing; Tamaulina Br. Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
The implementation of space cooperation is a collaborative effort between countries to carry out exploration and research projects in outer space. It involves the exchange of technology, resources, and knowledge to achieve common goals in space exploration. Space cooperation between Indonesia and China has become the focus of attention in recent years. In this article, I analyze the implementation of space cooperation between Indonesia and China using the 4 parallel mission scheme. This scheme involves four space missions running in parallel and the Indonesian Government (LAPAN), this includes satellite development, lunar exploration, scientific research and astronaut training. I explained the process of implementing this collaboration, the benefits that had been achieved, and the challenges faced in its implementation. This research is based on data and information collected from reliable sources, including official reports from both countries